APPLICATION OF PEDAGOGICAL QUALIMETRY IN MODERN MONITORING RESEARCH - Makarenko І.Є. (Pedagogy of Higher and Secondary Education, 2022)
The article deal with the essence of pedagoеcal qulimetry, its role in increasing the еffectiveness of monitoring reseаrches and aso it present the main theoretical propositions of qualimetric approach.